#TITLE_ALTERNATIVE# - Gunawan (NIM 122 03 047), Indra
Abstract: The prediction of production optimization of a gas well over certain time intervals need a proper selection of the production components. For that purposes usually the conventional nodal system analysis is used. However, the drawback of the conventional nodal system analysis is that the method doesnt consider any changing in the components of well production system. Therefore, if there are any changes the prediction of the well production as a function of time could not be well conducted. There is a method that consists of the combination between conventional nodal system analysis, material balance method, and decline curve analysis. This method is capable to optimize and predict production of a well under existing conditions as well as altered conditions. This paper presents the application of the dynamic nodal system analysis on well X-3.